William S. Breibart, Phyllis N. Butow, Paul B. Jacobsen, Wendy W. T. Lam, Mark Lazenby, Psyho-Oncology (4ª edición). Matthew J. Loscalzo (Editores), Nueva York, Oxford, 2021. - Sanz Cortés, Ana (Psicooncología, 2022)
Reseña de la obra de William S. Breibart, Phyllis N. Butow, Paul B. Jacobsen, Wendy W. T. Lam, Mark Lazenby, Psyho-Oncology (4ª edición). Matthew J. Loscalzo (Editores), Nueva York, Oxford, 2021.